(untitled) (Panacea Journal of Medical Sciences, 2024)
Chronic osteomyelitis is multifactorial in its occurrence, type, severity and prognosis. Presentation of chronic osteomyelitis may be varied even very unlike of its prototype. Cases of osteomyelitis were encountered caused by Nocardia brasiliensis, Actinomyces spp., Aspergillus flavus, Staphylococcus aureus, Morganella morganii with unusual presentations. The organisms except Staphylococcus aureus were among the seldomly reported ones. Two of the cases were found to be biofilm associated as studied by biofilm detection throughatomic force microscopy and methods of Anderl et al and Stepanovic et al. Only one case,c aused by biofilm producer strain of No cardia brasiliensis, required surgical correction with amputation. Rest four cases were recovered with antimicrobial therapy. Strong degree of suspicion of biofilm development and involvement of unusual etiological agents were required to diagnose and treat the cases of chronicity. It could put aside the drastic decisions like amputation which might be associated with immense eco-socio-psychological impact onthe patients and their families.